Brand Image Analysis Has a Positive Influence on Customer Satisfaction - Syadi Ismallah; Istaz Qasim (JINGLER : Jurnal Teknik Pengolahan Pertanian, 2023)
Maxx Coffee, established since 2015, is an original coffee shop chain from Indonesia. Maxx Coffee is a new brand, but is growing fast. It has opened 70 shops in Indonesia, and has five outlets in Surabaya. The rapid growth of coffeehouse retailers in Indonesia is affected by the modern lifestyle in society. In 2014, the numbers of registered coffeehouses in Indonesia reached 200 entrepreneurs compared to 100 entrepreneurs in the previous year (Global Business Guide Indonesia, 2014). However, there is no exact data regarding the amount of the coffeehouse in Surabaya.